The prevalence and risk factors of occult stress urinary incontinence in women undergoing genitourinary prolapse surgery - Jibril AH,; Ab Latip N,; Ng Pei Yuen,; Jegasothy R, (Faculty of Medicine, UKM Medical Centre, 2016)
De novo stress urinary incontinence (SUI) may occur in up to 80% of clinically continent women following genitourinary prolapse surgery. This had resulted in an increase in the rate of concurrent continence surgery during prolapse repair from 38% in 2001 to 47% in 2009 in the United States. To date, there is no local data available to estimate the prevalence of occult SUI (OSUI) among Malaysian women awaiting surgery. Therefore, this study was conducted to elicit the prevalence of occult SUI and its associated risks factors in patients awaiting prolapse surgery. We retrospectively studied the records of 296 consecutive women with significant pelvic organ prolapse awaiting reconstructive repair. All patients attended the Urogynaecology Unit in Hospital Kuala Lumpur Malaysia between October 2007 and September 2011. They had undergone standardized interviews, clinical examinations and urodynamic studies. During the urodynamic testings, all prolapses were reduced using ring pessaries to elicit OSUI. Primary outcome was the prevalence of OSUI with prolapse reduction to predict possibility of developing de novo SUI following prolapse surgery. Secondary outcome was the assessment of potential risk factors for OSUI. Among the 296 women studied, 121 (40.9%) were found to have OSUI. The risk factors associated with OSUI included age, BMI, numbers of SVD, recurrent UTI, reduction of urinary flow symptoms and grade 2 to 4 central compartment prolapses. We concluded that preoperative urodynamic testing with reduction of prolapse is useful to identify women with OSUI. This is important for preoperative counselling as well as planning for one step approach of prophylactic concomitant anti-incontinence procedures during prolapse surgery in order to avoid postoperative de novo SUI.